Ethnobotanical survey and phytochemical screening of anti-snakebite plants used in Bissok District of Gabon - Line Edwige Mengome; Ludovic Mewono; Raymonde Mboma; Jean Engohang-Ndong; Sophie Aboughe Angone (Society for Indonesian Biodiversity, 2021)
Abstract. Mengome, Mewono L, Mboma R, Engohang-Ndong J, Angone SA. 2021. Ethnobotanical survey and phytochemical screening of anti-snakebite plants used in Bissok District of Gabon. Biodiversitas 22: 3264-3275. Snakebites remain a major health issue in tropical and subtropical regions in the world. The limited access of antivenom sera in remote areas of many countries forces populations to rely on plant-based remedies to manage snakebite-induced injury. In this study, we conducted an ethnobotanical survey of medicinal plants used for the management of snakebites in the district of Bissok (Northern Gabon). After collecting and verifying the authenticity of the plants, we further performed their phytochemical analysis. The procedure used in this study involved a structured questionnaire and direct interviews of local populations. Overall, data collected on-site included local names, the part of the plant used, the preparation, and the route of administration. The presence of some phytochemical compounds was determined according to standard methods. Overall, a total of 29 species of plants belonging to 20 different families were reported to be used to treat snakebites. The plants used were herbs (44.80%), trees (24.10%), shrubs (20.70%), liana (10.30%), and rhizomes (6.90%). They were mainly used as poultice or crush, and to a lesser extent as decoction and maceration. Regarding the route of administration, interviewees reported mainly external use on the site of the bite. Concerning the chemical composition, we found that the antivenom plants were rich in chemical compounds known to have antivenom, antipyretic and antimicrobial properties, e.g. alkaloids, terpenoids, flavonoids, steroids, coumarins, phenols, tannins gallic Our results open avenues to develop venom enzyme inhibitory assays.